The Multiple Identities of Penghayat: Cilacap and the Moral Politics Issues on the Failure of their Candidate in 2019-Election - Khoirnafiya, Siti (Political Science Program, Universitas Negeri Semarang, 2020)
This article discusses the 2019 Indonesiaâ€™s election with the minority group issues ofÂ Penghayat. This research discusses their participation in elections, not only as voters but as the candidate nominated by them. However, the candidate nominated by them failed to become members of the DPRD although according to their estimation, the number of voters exceeded the target. An important factor that the failure tendency is related to the multiple identitiesâ€™ issues, which are not only related to ethnicity and religion but also moral politics. This paper does not only criticize the idea of identity politics which describes the uniformity of identity but also criticizes political practices that negate morality.